The Impact of ASEAN+6 Sustainable Policies on Indonesia’s Cocoa Butter Trade - Danendra Daffa Ibra; Hidayat Nia Kurniawati; Amanda Dea (BIO Web of Conferences)
The expansion of Free Trade Agreements (FTAs) within the ASEAN+6 region has reshaped economic dynamics, particularly in the trade of strategic commodities such as cocoa. As a vital tropical agricultural product, cocoa especially cocoa butter holds the largest market share potential in ASEAN+6 trade. These FTAs not only drive trade creation and diversion but also emphasize sustainability in resource management and environmental responsibility. This research explores the scope of ASEAN+6 agreements, trade policies, and their effects within the region using a descriptive qualitative approach and panel data regression with the Poisson Pseudo Maximum Likelihood (PPML) estimator. Findings reveal six active FTAs—AFTA, ACFTA, AIFTA, AKFTA, AANZFTA, and AJCEP regulating both tariff and non-tariff measures with sustainability considerations in political, economic, and environmental spheres. Empirical analysis highlights trade creation effects on Indonesia’s cocoa butter exports and imports, yet policy harmonization remains crucial to maximizing trade benefits and addressing sustainability challenges. Strengthening economic integration through a comprehensive regional review is imperative to align policies and enhance trade contributions to sustainable economic growth. By addressing gaps in literature and policy, this study underscores the necessity of integrated trade strategies to fortify ASEAN+6 economic resilience.